Minimum Weight Design of Composite Panel Under Aeroelastic Constraint - Shinya Honda; Gaku Yokoyama (Center of Techonolgy (COT), Engineering Faculty, Hasanuddin University, 2018)
The present study minimizes the number of layers of wing shaped plates fabricated by laminated composite (CFRP) under aeroelastic constraint which keeps stable flutter speed. The finite element analysis (FEA) for the aeroelastic characteristics requires considerable calculation effort. Therefore, the response surface method (RSM) is utilized to reduce the computational time for optimization where an approximate expression uses bending rigidity of composite plates as input and flutter speed as output. Then, distributed genetic algorithm (DGA) is employed as an optimizer and minimizes numbers of layers of composite plates by designing fiber orientation angles. The optimum wing model shows large amount of weight reduction and enough flutter speed in less computational time than without RSM.